1996
DOI: 10.5636/jgg.48.1145
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Air Sampling System for Measurements of the Concentrations of Stratospheric Trace Gases and Their Isotopic Ratios over Antarctica.

Abstract: In order to measure the concentrations of trace gases such as C02, CH4, N20 and halocarbons and the isotopic ratios of 513C, 5180 and A14C of CO2 in the stratosphere over Antarctica in January 1998, a balloon-borne cryogenic air sampling system was developed on the basis of the sampler which has used for the collection of stratospheric air over Japan since 1985. The sampler developed in this study is capable of collecting air samples with volumes of 20-30 lsTp at 12 height levels. Special attention was paid to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Stratospheric whole air samples were collected during six balloon flights over Sanriku, Japan (39 • N, Honda et al, 1996;Aoki et al, 2003;Honda, 2001). Herein, we describe them briefly.…”
Section: Sampling and Sample Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Stratospheric whole air samples were collected during six balloon flights over Sanriku, Japan (39 • N, Honda et al, 1996;Aoki et al, 2003;Honda, 2001). Herein, we describe them briefly.…”
Section: Sampling and Sample Storagementioning
confidence: 99%
“…The air sampling system can collect multiple whole-air samples into pre-evacuated 760 cm 3 stainless steel sample bottles. Chemical and isotopic compositions in the sampled air are only slightly affected by the collection process (Honda et al, 1996;Honda, 2001). Preliminary experimental tests showed that a possible change of δ 18 O CO 2 caused by isotope exchange between CO 2 and water on the inner walls of the sample bottle is comparable to our analytical precision of 0.05‰ (Honda, 2001;Gamo et al, 1995;Aoki et al, 2003).…”
Section: Sampling and Sample Storagementioning
confidence: 99%
“…In the present study, air sampling was performed during balloon ascent. In the past, we conducted a number of similar air samplings using a cryogenic sampler with liquid helium (Honda et al, 1996) in which we collected samples during the balloon ascent and descent over Japan; they showed that the outgassing from the balloon and payload had a negligibly small impact on the air sample quality even if air sampling was made during the balloon ascent (Morimoto et al, 2009;. One sampler assigned to 21 km leaked after landing due to a defect in electric circuit.…”
Section: Methodsmentioning
confidence: 99%
“…Air samplcs for the N20 and CH 4 analyses were also collected by cryogenic samplers from the University of Frankfurt [Schmidt et al, 1987] and Tohoku University [Honda et al, 1996] on board balloons launched from Kiruna on February 11 and 22, respectivcly. Air samples were collected between 10 and 27 km, mostly during descent, and they were analyzed in the laboratory using gas chromatography.…”
Section: Introductionmentioning
confidence: 99%